Front Cover Picture: Iridium(I) Complexes with Anionic N‐Heterocyclic Carbene Ligands as Catalysts for H/D Exchange in Nonpolar Media (Adv. Synth. Catal. 18/2020). Issue 18 (29th July 2020) - Koneczny, Marvin; Phong Ho, Luong; Nasr, Alexandre; Freytag, Matthias; Jones, Peter G.; Tamm, Matthias
Abstract : The front cover picture, provided by Matthias Tamm and co‐workers and designed by Mailin Röder, illustrates a new class of stable iridium(I) complexes with N‐heterocyclic carbenes (NHC) bearing a weakly coordination anionic borate moiety. This piggyback B(C6 F5 )3 unit affords neutrally charged iridium catalysts for efficient deuteration of various substrates with D2 gas in nonpolar solvents. Details can be found in the full paper on pages 3857–3863 (M. Koneczny, L. P. Ho, A. Nasr, M. Freytag, P. G. Jones, M. Tamm, Adv. Synth. Catal . 2020, 362, 3857–3863; DOI: 10.1002/adsc.202000438 ).